(3E)-3-(4-(Dimenthylamino)Phenyl)-1-(4-Hydroxyphenyl)Prop-2-En-1-One - Hasan, Aurangzeb; Akhtar, Nadeem; Lajis, Md Nordin; Rusli, Aqilah Fasihah; Kong, Mun Lo (PubMed Central, 2010)
The asymmetric unit of the title compound, C17H17NO2, contains two crystallographically independent molecules. Both molecules adopt a trans configuration about the C=C bond, with the C—C=C—C fragments in the two molecules twisted in opposite directions [torsion angles of 174.2 (2) and −175.8 (2)°]. The two benzene rings in each of the molecules make dihedral angles of 20.21 (6) and 48.64 (4)°. In the crystal, adjacent molecules are linked by O—H[cdots, three dots, centered]O hydrogen bonds into infinite polymeric chains.